2019
DOI: 10.1177/0268396219870548
|View full text |Cite
|
Sign up to set email alerts
|

The negotiated order and electronic patient records: A sociomaterial perspective

Abstract: In this article, we consider how the notion of the negotiated order can be reinterpreted by drawing on ideas from sociomateriality. We argue that the negotiated order is an ongoing accomplishment in which a heterogeneous set of situated sociomaterial practices (or actors) are implicated. To do this, we draw upon an in-depth study of the use of a computerised physician order entry system in a hospital in Saudi Arabia. We explore how a computerised physician order entry system, as a new sociomaterial actor, perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 65 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Another deficiency of the current sociomateriality literature relates to the work arrangements that have been investigated: most studies have been conducted in relatively homogeneous contexts with a focus on single technologies used by co-located actors (Dourish and Mazmanian, 2013;Scott and Orlikowski, 2012). While some studies include multiple technologies (Contractor, Monge and Leonardi, 2011) and others consider distributed work across organizations (Introna, Hayes and Al-Hejin, 2019;Pelizza, 2021), we found no study of work arrangements where actors use multiple technologies to conduct work across organizational boundaries. Consequently, there is a need to further advance our understanding of digital technology in sociomaterial inquiry (Leonardi and Barley, 2010;Mutch, 2013), and especially to characterize the ways technology is used in heterogeneous work arrangements where distributed actors employ diverse technology portfolios to produce and consume information across organizational and technological boundaries.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Another deficiency of the current sociomateriality literature relates to the work arrangements that have been investigated: most studies have been conducted in relatively homogeneous contexts with a focus on single technologies used by co-located actors (Dourish and Mazmanian, 2013;Scott and Orlikowski, 2012). While some studies include multiple technologies (Contractor, Monge and Leonardi, 2011) and others consider distributed work across organizations (Introna, Hayes and Al-Hejin, 2019;Pelizza, 2021), we found no study of work arrangements where actors use multiple technologies to conduct work across organizational boundaries. Consequently, there is a need to further advance our understanding of digital technology in sociomaterial inquiry (Leonardi and Barley, 2010;Mutch, 2013), and especially to characterize the ways technology is used in heterogeneous work arrangements where distributed actors employ diverse technology portfolios to produce and consume information across organizational and technological boundaries.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In the medical field, research has already shown the many significant implications that arise when a new technology is adopted, such as task redistribution between humans and nonhumans (Morland and Pettersen, 2018; Nicolini, 2010; Star, 1999), a renegotiation of medical work practices (Introna et al, 2019), and a change of the discursive practices involved in telemedicine (Gherardi, 2010). However, while more extensive research focuses on specific medical professions, such as surgery and pharmaceutics (Barrett et al, 2012; Beane, 2019; Korika and Molloy, 2010; Menchik, 2020), less attention has been paid to studying how robots enter the everyday practices of rehabilitation work.…”
Section: Related Researchmentioning
confidence: 99%
“…For example, Jones (2014) investigates the adoption of a computer based clinical information system in a hospital critical care unit showing how a transformation from paper to electronic records through material-discursive practices “bring into play power relations, norms, and understandings (of experiences, of competencies, of medical knowledge) and evoke emotions (of fear, of interest, of relief)” (Jones, 2014, p. 915). Likewise, Polykarpou et al (2018) explore practitioners' justification of health IT investments, Timmons et al (2019) analyzes radio pagers implemented to prevent older adults' bedside falls in hospitals, while Introna et al (2019) examines a computerized physician order entry system in a hospital context. Hultin and Mähring (2017) show how material-discursive analyses can be applied to analyzing digital and physical visualization boards.…”
Section: Discourse and Materiality In Organization Studiesmentioning
confidence: 99%